The importance of education in the formation of youth civil activity in the higher education system - Muratov, Habibulla (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article can be useful as a source to study the formation of civic activism of young people in higher education on the basis of a systemfunctional approach, to highlight the practical significance of reforms in the education system, to study the mechanisms of achieving quality and effectiveness of education